Podaż i spożycie kawy w Polsce w latach 1950-1995 - Zajączkowska, Maria (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1997)
The consumption of coffee in Poland in the last 35 years increased 14 times. Between 1989 and 1995 it doubled. In the centrally planned economy, the supply of coffee was determined by the government planning office regardless of the fact that the demand was not met. Until the end of the seventies better quality coffee beans /arabica/ were imported from Brazil. Prom the beginnings of the nineties the quality of imported coffee worsened. In market economy the supply of coffee is determined by the demand. Since 1993 the coffee market has become stabilized while the demand has shifted in the direction of better quality coffee sorts. Apart from the world brands /such as Jacobs, Tchibo, and others/ 140 small coffee roasting firms exist on the market. Poles prefer ground coffee. More coffee is consumed in the households of the retired people, whereas the least in those of farmers. On the average, in 1996 slightly over one and a half kilogram was consumed per person annually.